Adaptive Materials: Rational Design of Mechano‐Responsive Optical Materials by Fine Tuning the Evolution of Strain‐Dependent Wrinkling Patterns (Advanced Optical Materials 5/2013). Issue 5 (28th May 2013) - Kim, Philseok; Hu, Yuhang; Alvarenga, Jack; Kolle, Mathias; Suo, Zhigang; Aizenberg, Joanna
<x xml:space="preserve">Abstract</x> Labyrinth and checkerboard wrinkle patterns appear in optical micrographs of oxidized poly dimethylsiloxane sheets taken by P. Kim, J. Aizenberg, and co‐workers when two orthogonally oriented stresses become vanishingly small. On page 381, vertically and horizontally aligned wrinkle patterns undergo abrupt switching over this narrow 'transition region', and their associated optical diffraction patterns also display the signature of orthogonally oriented domains. Image courtesy of P. Kim and J. C. Weaver at Harvard University. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>